Análise e controle de um veículo robótico tracionado por esteiras - Santos, Alexsandro José Virgínio dos (2015)
The use of unmanned vehicles has been widespread in the areas of safety, environmental exploitation and industry in general and can be tele-operated or autonomous. There are also hybrid systems, in which the vehicle is tele-operated, but endowed with intelligent algorithms that guide the operator and make decisions in the most critical situations. Many authors have studied the kinematics and the dynamics of traction vehicles per mat, with a consensus that the kinematic model can be simplified to most analyzes. Most studies using vehicles pulled by mats near the kinematic model of a wheeled vehicle with differential drive. In this paper we proposed an unconventional approach, in which the kinematic model is treated as a flexible body. Is based on the fact that, in a curvilinear motion, there is a point of contact equivalent to a wheeled vehicle to a given instant. The dynamic model proposed in this work includes the lateral drag force to cause the tracks of curvilinear motions, considering its non-linearity and strong coupling between the mats. Even as contribution of this work, we present the implementation of a control system able to identify the soil adhesion characteristics and perform control strategies for the vehicle from the track/soil interaction.